Fenomen krize identiteta u srpskom romanu 19. i 20. veka - Raičević, Gorana (Slavistična revija, 2011)
This paper is based on a diachronic analysis of the phenomenon of identity crisis - an important but insufficiently studies characteristic of the 19th- and 20-century Sebian novel. The research results indicate that the identity crisis inevitably leads undividuals into a (self)destructive conflict with the patriarchal collective, whose value system is the source of frustration for a number of male and female characters in the novels that marked Serbian literature during the past two centuries.
Keywords: 19./20. st.; kriza identitete; novel; patriarhalna družba; roman; srbska književnost